# math

posted by .

Please show the steps and explain how to do this as well.
3√8 · 2√5

• math -

3 sqrt ( 8 ) * 2 sqrt ( 5 ) =

3 * 2 * sqrt ( 8 ) * sqrt ( 5 ) =

6 sqrt ( 8 * 5 ) =

6 sqrt ( 40 ) =

6 sqrt ( 4 * 10 ) =

6 sqrt ( 4 ) * sqrt ( 10 ) =

6 * 2 * sqrt ( 10 ) =

12 sqrt ( 10 )

• math -

thank you so much :)

## Similar Questions

1. ### Algebra

How would i complete these problems? 1. (√6mn)^5 2. ^3√16x - ^3√2x^4 3.^4√x • ^3√2x 4. ^3√72x^8 5. √63a^5b • √27a^6b^4 and are these problems correct?
2. ### Math

Find an equation of the line that bisects the obtuse angles formed by the lines with equations 3x-y=1 and x+y=-2. a. (3√2 +√10)x-(√10 + √2)y-2√10+√2=0 b. (3√2 - √10)x+(√10 - √2)y+2√10+√2=0 …
3. ### maths

I will be thankfull to you if you help me to solve the below problem: 6√x-11/3√x=2√x+1/√x+6 I tried to solve the above problem like this: (6√x-11)(√x+6)=(3√x)(2√x+1) 6√x(√x+6)-11(√x+6)=(3√x)(2√x)+(3√x)(1) …

Please show work Simplify rational 1. 4√(a^6 b^13) / 4√(a^2b) 2.√(2x^3 / 49y^4) Add or Subtract 3. x√(75xy) - √(27x^3y) Multiply 4.(√(5) - 5) (2√(5) + 2) Rationalize the denominator 5. √(25x^5 …
5. ### algebra

Multiply and simplify. Assume that no radicands were formed by raising negative numbers to even powers. √6x^3 * √18x^2 = √2 * 3 * x^3 * √2 * 3^2 * x^2 = √2 * 3x^2x * √2 * 3^2 * x^2 = 6x^2 * √3x …
6. ### algebra

Multiply and simplify. Assume that no radicands were formed by raising negative numbers to even powers. √6x^3 * √18x^2 = √2 * 3 * x^3 * √2 * 3^2 * x^2 = √2 * 3x^2x * √2 * 3^2 * x^2 = 6x^2 * √3x …